(3bGYOI eTQhYjI GdOdjd GdLfGFi (B: s (3OGQSI ebGQfI (B/ s - (3gGHS YThi GdYfRis; (3CMeO aJMi SQhQs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2018)
(3Ef eHOC SjGOI GdbGfhf gh YfhGf GdOhdI GdbGfhfjI(B: (3h eaGOg EdJRGe LejY CaQGO GdTYH McGekG h eMchejf h SdWGJ GdOhdI Ydi GdShGA HGdNVhY ddbGfhf cCSGS deTQhYjI GdCYeGd GdJi jbhehf HgG(B: (3h Ef GdTQYjI GdELQGFjI JMJd ecGfI YGdjI HGdOSJhQ chfgG QcjRg ddOhdI GdbGfhfjI h VeGfkG CSGSjkG ddeMGceI GdLfGFjI GdefUaI(B: (3hEf GdTQYjI GdELQGFjI JCJi ef eHOC CUd GdHQGAI ai GdeJge(B: (3h GdOdjd GdLfGFi gh GdgOa GdJi jJLg Edjg GdEKHGJ GdLfGFi(B: (3h jQJcR Ydi cd GdhbGFY h GdCYeGd GdbGfhfjI GdJi JNOe LgJi GdGJgGe h GdOaGY(B: (3h Ef eQMdI EfJGL GdOdjd Ch LeYg gi eLehYI GdELQGAGJ GdJi JgOa Edi GdcTa Yf GdMbjbjI(B: (3h Yf KHhJ GdJgeI h ef Ke fSHJgG ddeJge(B: (3h JYJHQ VeGfGJ GdeTQhYjI ai eQMdI EOGQI GdOdjd h gi eQMdI GdJMbjb GdGHJOGFi h eQMdI GdeMGceI ef Cge GdELQGAGJ GdELQGFjI GdegeI h GdMjhjI(B: (3agi GdJi JJYQV ajgG MQjI h Mbhb GdCaQGO ddeSGS(B: (3h Ydjg jLH Cf JMGW gPg GdELQGAGJ GdNWjQI HSjGL ef GdVeGfGJ MJi JeGQS HTcd jVef GdehGRfI Hjf Mb GdeLJeY ai GdhUhd Edi GdMbjbI h YbGH GdePfH habkG ddELQGAGJ GdbGfhfjI GdUMjMI(B: (3Ef GdLRGA GdELQGFi jQO Ydi GdYed GdELQGFi(B: (3h jgOa Edi MeGjI GdbhGYO GdELQGFjI h VeGf MSf EOGQI GdYOGdI GdLfGFjI h GMJQGe Mbhb GdeJge h MQjGJg(B: (3cPdc aEf GdLRGA GdELQGFi jeVf GMJQGe GdTQYjI GdELQGFjI(B: (3EYeGdkG deHOC SjGOI GdbGfhfs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2018s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B585-622s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdOdjd GdLfGFis; (3SjGOI GdbGfhf s; (3eTQhYjI GdOdjd GdLfGFi s; (3TQhW GdeTQhYjIs; (3JWhQ GdGOdIs; (3GdMeV Gdfhhjs; (3eGgjI GdJMbjb GdGHJOGFjs; (3VeGfGJ GdeTQhYjIs; (3YdGfjI GdeMceIs; (3GdLRGA GdGLQGFjs; (3bHhd hGSJHYGO GdGOdI s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs